Guarantees of public utilities declaration between the rule and the exception in Algerian Law - Khelifi, Chaouki; Rebbahi, Mostafa (Journal of Human Sciences, 2023)
In accordance with the law regulating expropriation; the public utility is declared according to two different mechanisms: One is the rule and the other is the exception.   As for the first mechanism which constitutes the basis (rule), it was regulated by law 91/11 of 04/27/1991 setting the rules relating to expropriation for reasons of public utility and its implementing texts before the modification, and it relates to the classical operations that fall outside the circle of infrastructure of public benefit and a national and strategic dimension.    As for the mechanism that constitutes the exception, it was regulated by the financial laws of 2005; 2008 and 2014, which supplemented Law 91/11; and it relates to the operations concerns infrastructures of public benefit and a national and strategic dimension.    According to this discrepancy in the mechanisms for declaring public benefits and the legal frameworks that govern them between the rule and the exception, the procedures, tools, and conditions necessary to adopt one without the other was differed, The matter which unleashed the administration's powers in this regard, which would threaten the guarantees of those expropriated in this regard (on the occasion of the public benefit declaration), Which we will try to verify through this study.